2017
DOI: 10.3390/ijms18040730
|View full text |Cite
|
Sign up to set email alerts
|

The Neutrophil/Lymphocyte Ratio at Diagnosis Is Significantly Associated with Survival in Metastatic Pancreatic Cancer Patients

Abstract: Different inflammation-based scores such as the neutrophil/lymphocyte ratio (NLR), the Odonera Prognostic Nutritional Index (PNI), the Glasgow Prognostic Score, the platelet/lymphocyte ratio, and the C-reactive protein/albumin ratio have been found to be significantly associated with pancreatic cancer (PDAC) prognosis. However, most studies have investigated patients undergoing surgery, and few of them have compared these scores. We aimed at evaluating the association between inflammatory-based scores and PDAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 25 publications
3
39
0
Order By: Relevance
“…In our study, initial NLR was significantly lower in LS patients with mPDAC. Those results are consistent with previous studies as the prognosis role of the NLR has been demonstrated in PDAC in both early and advanced stages . NLR should be considered a stratification factor in further clinical trials in order to determine whether patients with high NLR at diagnosis could benefit from intensified treatment or, on the contrary, should only require palliative treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, initial NLR was significantly lower in LS patients with mPDAC. Those results are consistent with previous studies as the prognosis role of the NLR has been demonstrated in PDAC in both early and advanced stages . NLR should be considered a stratification factor in further clinical trials in order to determine whether patients with high NLR at diagnosis could benefit from intensified treatment or, on the contrary, should only require palliative treatment.…”
Section: Discussionsupporting
confidence: 92%
“…NLR is a biomarker of systemic inflammatory response and has been identified as an important prognostic factor for a number of malignancies, including colorectal cancer, renal cell carcinoma, and non‐small cell lung cancer . Elevated NLR at diagnosis has been strongly associated with worse progression‐free survival and OS . The inflammatory response plays an important role in cancer development and progression .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to identify a valid, cost-effective, and reliable prognostic predictor that is available before treatment. In recent years, pretreatment subsets of peripheral blood cells, including lymphocytes, neutrophils, monocytes, and platelets, have been found to be associated with the prognosis of various cancers [ 13 , 14 , 15 , 16 , 17 ]. Pretreatment neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) can be regarded as 3 representative systemic inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%
“…In mPC, NLR (cutoff: ≥3.75) was confirmed to be associated with decreased OS and may serve as a useful combination marker to enhance the prognostic value of CA 19-9 (cutoff: ≥626 U/ml) alone, with an Area un-der the Curve (AUC) of 0.843 when these two values were combined [65]. The prognostic value of NLR has also been confirmed in a recent Italian study, with an NLR cutoff of >5 [66]. Regarding the prognostic value of preoperative C-reactive protein (CRP), evidence for some time has been less clear since studies on resectable PC reported conflicting results, as summarized in a previous systematic review [67].…”
Section: Clinical Factors and Blood Markers In Mpc Patientsmentioning
confidence: 68%